2022
DOI: 10.1002/clc.23753
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety is associated with higher recurrence of atrial fibrillation after catheter ablation: A meta‐analysis

Abstract: Previous studies that evaluated the influence of anxiety on recurrence of atrial fibrillation (AF) after catheter ablation showed inconsistent results. We performed a meta‐analysis of cohort study to systematically evaluate the association between anxiety and AF recurrence after catheter ablation. Electronic databases of PubMed, Embase, and Web of Science were searched for relevant cohort studies from inception to January 20, 2021. We applied the random‐effect model to combine the results to incorporate the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…However, our study did not find a causal relationship between anxiety disorder and AF. Although previous studies generally suggest a positive association between anxiety and the risk of AF, 40 subsequent findings have yielded inconsistent results. A meta‐analysis of 11 cohort studies reported no significant association between psychological factors such as anxiety, depression, anger, work stress, and the risk of AF 41 .…”
Section: Discussionmentioning
confidence: 86%
“…However, our study did not find a causal relationship between anxiety disorder and AF. Although previous studies generally suggest a positive association between anxiety and the risk of AF, 40 subsequent findings have yielded inconsistent results. A meta‐analysis of 11 cohort studies reported no significant association between psychological factors such as anxiety, depression, anger, work stress, and the risk of AF 41 .…”
Section: Discussionmentioning
confidence: 86%
“…However, AF recurrence after CA is not uncommon. Several factors are believed to be implicated, including structural heart disease, left atrium characteristics (diameter, voltage), PV isolation-reconnections, AF duration, the presence of non-PV triggers, cardiometabolic risk factors, chronic kidney disease, and anxiety [ 27 , 28 , 29 ]. Interestingly, AF ablation in the CABANA randomized clinical trial led to reductions in left atrial volume index and mean PV ostial diameter, which were associated with lower AF recurrence rates [ 30 ].…”
Section: Atrial Fibrillation Catheter Ablationmentioning
confidence: 99%
“…found that depression was associated with a significantly increased risk and cumulative incidence of new-onset AF ( 14 ). A meta-analysis of cohort studies demonstrated that anxiety was independently associated with an increased risk of recurrence of AF after catheter ablation (adjusted relative risk, 2.3; 95%CI, 1.710-3.260; P < 0.001) ( 15 ). One study demonstrated that the level of anxiety before coronary artery bypass surgery is an important factor in the development of AF after surgery ( 16 ).…”
Section: Introductionmentioning
confidence: 99%